2020
DOI: 10.12973/ijem.6.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Middle School Students’ Self-Regulation Skills and Vocabulary Learning Strategies in Foreign Language

Abstract: The purpose of the current study is to investigate middle school students' self-regulation skills and vocabulary learning strategies in foreign language. The sampling of the current study consists of 990 5th, 6th, 7th and 8th grade middle school students attending state middle schools in the Mentese district of the city of Mugla, Turkey in school year 2018-2019. As the data collection tools, the Perceived Self-Regulation Scale and the Vocabulary Learning Strategies in Foreign Language Scale were used. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Besides, the role of gender, grades, learning environment, and age context on vocabulary learning strategies has also been investigated. However, similar to the previous variable, studies on the relationship between vocabulary learning strategies and gender found mixed and inconsistent results, such as in (Bhatti & Mukhtar, 2020) and (Gorgoz & Tican, 2020). The previous studies in the Indonesian context did not connect the VLSs to individual differences such as gender.…”
Section: Introductionsupporting
confidence: 55%
“…Besides, the role of gender, grades, learning environment, and age context on vocabulary learning strategies has also been investigated. However, similar to the previous variable, studies on the relationship between vocabulary learning strategies and gender found mixed and inconsistent results, such as in (Bhatti & Mukhtar, 2020) and (Gorgoz & Tican, 2020). The previous studies in the Indonesian context did not connect the VLSs to individual differences such as gender.…”
Section: Introductionsupporting
confidence: 55%
“…The 2011 English curriculum differs from the previous versions by elevating the importance of students' learning motivation, the communicative and practical competency of language learning, and pleasure reading for life (Hu & Adamson, 2012). And there are also numerous research studies suggesting how learning motiviation and interest lead to better learning outcome (Abbott et al, 2017;Gorgoz & Tican, 2019). The instruction in the secondary school classrooms in these rural districts in Beijing, however, failed to address this important aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Bandura (as cited in Mahmoud & Matar, 2011, p. 205) stated that "people are able to regulate themselves through direct control over their behaviors and through selecting or changing the environmental conditions that in turn affect their behaviors, thus creating their own incentives that drive and lead their behavior". Gorgoz & Tican (2020) revealed that, with age, students become free and more independent, have more developed selfregulation skills, and conduct their learning in a more planned and conscious manner. This is confirmed by the study of Assabab (2016) in that self-regulated students are distinguished by having many ways in which they organize their motivation as well as set suitable goals for their abilities and their surrounding conditions.…”
Section: Self-regulationmentioning
confidence: 99%